LEGAL RAMIFICATIONS OF DISPUTES CONCERNING THE OUTER LIMITS OF THE CONTINENTAL SHELF IN THE ABSENCE OF CLCS RECOMMENDATIONS - Xubing Li, (PEOPLE: International Journal of Social Sciences, 2025)
The United Nations Convention on the Law of the Sea (UNCLOS) Article 76 and Annex II, Section 7, specify the procedures for the delineation of the continental shelf, requiring coastal states to submit scientific and technical data to the Commission on the Limits of the Continental Shelf (CLCS) to demonstrate the extent of their continental shelf. In practice, some states have exercised authority over the continental shelf beyond 200 nautical miles without obtaining recommendations from the CLCS or have been rejected by the CLCS. These states argue that the recommendations of the CLCS are not decisive in delineation. Some of these states have even received support from international court judgments, sparking discussions on the effectiveness of CLCS recommendations and controversies over the validity of delineation beyond 200 nautical miles. This paper argues that since states have inherent rights to their territories, the absence of CLCS recommendations does not preclude them from claiming rights to these areas. In cases of litigation arising from delineation beyond 200 nautical miles, if a state can provide sufficient evidence to prove that its territory indeed extends beyond 200 nautical miles and that its delineation does not exceed the actual limits of its continental shelf, the international court will support the state. However, the court’s support does not equate to the validity of the delineation, valid delineation must still adhere to the procedures stipulated by UNCLOS.